Perlindungan Hukum Terhadap Nasabah Kaitannya dengan Lembaga Penjamin Simpanan - Switkar Putri, Tadevin (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 2 (2019), 2019)
A relation between customer with the bank is only based on the trust, it was not generally balance because the real understanding note just coming from one side which is only from the bank. This unbalanced risk make their debit at the dissolved bank become a common priority to be given, it is very important to provide a legal protection for customers and this is deemned to be studied further based on the perspective of legal protection for customer. From those explanation there is a blurring norms. This research was reviewed based on normative legal research with a legal approach, conception approach, and analytical provisions. The legal materials are sourced from primary, secondary and tertiary materials. Legal materials are collected using snowball system techniques and analyzing legal materials using description technique and interpretation technique. The purpose of this research is to elaborate on the public to understand the regulation of bank customer protection, and understand about the protection of customer which is not covered by LPS. The result of the study concluded that : there was certainty of way out from the problematic or dissolved bank, namely by completing based on article 6 paragraph (2) of the LPS law, this also resolving the problem of crisis against the economy. To protect the norms to save the consumers in related to heir savins which is not borne by LPS, can be specified in accordance with the fabric of bank norms for consumers save which is based on the agreement and based on non contractual relation. Hubungan antara nasabah dengan bank hanyalah berlandaskan atas kepercayaan, maka dalam kedudukannya hal ini menjadi hal yang tidak seimbang. Akibatnya lahirlah sebuah kesepakatan riil satu arah yaitu oleh bank. Tidak setaranya resiko ini menjadikan debit persediaan konsumen bagi institusi ini yang sudah dibubarkan bukanlah menjadi hal pokok untuk dipenuhi, hingga konsumen dianggap krusial untuk mendapatkan perlindungan hukum dan dianggap perlu untuk hal ini dikaji lebih lanjut dari sudut pandang perlindungan hukumnya terhadap konsumen. Dari penjelasan itu terjadi kekaburan norma. Penelitian ini ditinjau dari penelitian hukum normatif dengan pendekatan perundang-undangan, ketetapan konsepsi, dan ketetapan analitis. Bahan hukum bersumber pada bahan hukum primer, sekunder dan tersier. Bahan hukum dikumpulkan dengan teknik sistem bola salju dan menganalisis bahan hukum menggunakan teknik deskripsi dan teknik interpretasi. Tujuan penelitian ini yaitu mengelaborasi dan memahami pengaturan perlindungan nasabah bank, dan paham tentang perlindungan nasabah yang tak ditanggung LPS.  Hasil studi memberi kesimpulan bahwa: adanya kepastian jalan keluar dari bank yang bermasalah maupun gagal yakni dengan menyelesaikan berdasarkan atas Pasal 6 ayat (2) UU LPS serta menyelesaikan masalah krisis terhadap perekonomian. Pengamanan norma-norma kepada konsumen penabung sehubungan tabungannya yang tiada ditanggung LPS bisa dirinci berdasarkan jalinan norma bank kepada konsumen penabung yakni atas dasar jalinan kesepakatan dan berdasarkan hubungan non kontraktual.